Adult spinal deformity–like sagittal malalignment treated with full endoscopic interspinous cleaning surgery in a patient with Baastrup’s disease: illustrative case - Seiya Watanabe; Hiroo Shiraga; Takeshi Hara; Saori Soeda; Daiki Nakajima; Hiroshi Kageyama; Junzo Fujitani; Masatoshi Morimoto; Hiroaki Manabe; Fumitake Tezuka; Koichi Sairyo (Journal of Neurosurgery: Case Lessons, 2026)
BACKGROUND Baastrup’s disease is a degenerative disorder characterized by contact between adjacent spinous processes and typically presents with extension-related low back pain. Although it is generally regarded as a localized posterior element disorder, its impact on global sagittal alignment remains unclear. OBSERVATIONS A 78-year-old man presented with severe low back pain, postural impairment, and adult spinal deformity (ASD)–like sagittal malalignment. Standing radiographs demonstrated a sagittal vertical axis (SVA) of 210 mm and a pelvic incidence–lumbar lordosis mismatch of 53.9°. He had previously been advised to undergo extensive corrective fusion surgery. MRI demonstrated interspinous inflammatory changes at multiple lumbar levels. Diagnostic Baastrup blocks identified the L3–4 interspinous lesion as the primary pain generator. Because repeated blocks provided only temporary relief, full endoscopic interspinous cleaning surgery was performed under local anesthesia. Low back pain resolved completely, the SVA improved from 210 mm to 48 mm, and the favorable outcome was maintained at the 1-year follow-up. LESSONS In patients presenting with severe ASD-like sagittal malalignment, careful identification of symptomatic Baastrup’s disease may reveal a reversible functional component. Diagnostic Baastrup blocks and full endoscopic interspinous cleaning surgery may allow selected patients to avoid unnecessary extensive fusion surgery. https://thejns.org/doi/10.3171/CASE26643